The reliability and validity of the rebound countermovement jump in National Collegiate Athletic Association Division I American football players - Talpey, S. W.; Drake, M.; Haintz, L.; Belanger, A.; O'Grady, M. W.; Young, W. B.; Mundy, P. D.; James, L.; Gabbett, T. J.; Gardner, E. C. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this study was to investigate the reliability and validity of the rebound countermovement jump (R-CMJ), as an alternate test of leg muscle function to the CMJ and drop jumps (DJs). Because the first phase of the R-CMJ mimics that of the CMJ, it is hypothesized that variables obtained in phase I of the R-CMJ will be like those of a CMJ. Similarly, because the second phase of a R-CMJ mimics a DJ, it is believed that the variables obtained from phase II will be like those from a DJ. Collegiate male American football players (N = 46) aged 18-24 years completed CMJs and R-CMJs on a portable force plate. Tests were completed on 3 separate days to determine the repeatability of select variables and to establish their validity. In addition, a subgroup (N = 20) of players from the cohort completed DJs from both 30 cm (DJ30) and 45 cm (DJ45) to determine the concurrent validity of the variables obtained from the second phase of the R-CMJ. Most variables obtained from the CMJ and R-CMJ phase I were found to be reliable, except for time-to-take-off. The variables from the DJ30, DJ45, and R-CMJ phase II displayed moderate to good reliability; however, all coefficient of variations were >10%. Jump height achieved in the CMJ was significantly greater than that achieved in phase I of the R-CMJ. The reactive strength index was significantly different in the R-CMJ compared with the DJ from both 30 and 45 cm heights. Although the R-CMJ may be inviting for coaches to use owing to its ease and time efficiency, the results of this study highlight that it may not provide a valid representation of an athlete's reactive strength.